Secondary market trading infrastructure of government securities - Csaba Balogh; Gergely Kóczán (Magyar Nemzeti Bank, 2009)
The subject of our study is the trading infrastructure of government securities markets, which has undergone fundamental changes driven by the appearance of non-exchange electronic platforms and the rapid rise of their share in the trading volume of developed markets. The summary of the relevant literature indicates that improved trading transparency clearly increases the efficiency of the market (its role in price discovery). Its effect on market liquidity, however, is less clear-cut. While the loss of anonymity most likely decreases liquidity, transparency on the quantity and price of concluded transactions enhances liquidity. The emergence of electronic trading on developed government securities markets has not changed the fundamental structure of trading, which continues to take place in two segments: between dealers (B2B) and between dealers and clients (B2C). There is, however, no interbank trading platform on the Hungarian government securities market, although data vendors and other platforms serving clients have sprung up. Nonetheless, more than 90 per cent of trading takes place through traditional OTC channels. Consequently, actors which are interested in market processes and prices, but do not actively trade on the Hungarian market have trouble accessing high-standard, quasi-real-time price information. The MiFID initiative - launched at the European level - may contribute to improving the Hungarian market's transparency by engendering the regulation of the bond market similar to that of the equity market. Introduction of the euro in Hungary will fundamentally change the country's market structure. The sovereign debt manager's leeway will increase, and the key direct actors on the government securities market are expected to be the major international actors, which are interested in the centralisation of government securities trading by currencies. Based on the broad electronisation of the euro-denominated government securities market, it is likely that electronic platforms will also gain ground on the Hungarian market, following the introduction of the single currency at the latest.
Keywords: G14; G15; D40; 330; government securities market; secondary trading; transparency; efficiency; market liquidity; Öffentliche Anleihe; Sekundärmarkt; Markteffizienz; Marktliquidität; Ungarn